A study on factors influencing employee engagement at Pejabat Setiausaha Kerajaan Negeri Sembilan / Mohd Syer Aidid Rusazman Sharan - Rusazman Sharan, Mohd Syer Aidid (Faculty of Business and Management, 2018)
Engaging right employees with their right behavior are the critical aspect faced by organization today. This engagement starts when a firm able to find, understand and manage those talented workers and strive to maintain it into a higher level of engagement. High level of employee engagement may guarantee not only the short-term survival of a firm but also the factor for a long-term business performance. Nevertheless, for employees act to be an engaged worker, neither employers not only prioritized on what they should do to ensure them to be engaged but employees are also eligible to say their wants in making them to be such accordance employees. The purpose that the researcher wanted to conduct this study is mainly to know the factors that would made employees to be engaged in the organization, thus, able to retain them for a long period of time. This study found out that those three independent variables which are leadership, compensation and working environment, had a relationship with employee engagement. Nevertheless, working environment is the most influence factor of employee engagement in this study.